High resolution thermal and multispectral remote sensing for detecting devitalized trees in Monarch Butterfly Biosphere Reserve - Guadarrama-León, Ramón; Sáenz-Romero, Cuauhtémoc; Rosas-Chavoya, Marcela; Méndez-Montiel, José T.; Lindig-Cisneros, Roberto A.; Blanco-García, Arnulfo; Gallardo-Salazar, Jose Luis (Forest Systems, 2026)
Aim of study: To identify different levels of devitalization in individuals of Abies religiosa (Kunth) Schltdl. & Cham. (oyamel) in the core zone of the Monarch Butterfly Biosphere Reserve (MBBR), using multispectral and thermal information captured with drone. Area of study: The study area, comprising 26 ha, is located within the federal property of the MBBR. This area also belongs to the core zone of the Protected Natural Area. Material and methods: Overflights were conducted with drones equipped with multispectral and thermographic sensors in monitoring plots. Using high-resolution images captured by drone and photogrammetric processing, the normalized difference vegetation index (NDVI), surface temperature (ST), and temperature-vegetation dryness index (TVDI) were calculated. These values were combined with field data to determine three different levels of tree devitalization (i.e., healthy, devitalized, and dead trees). Main results: The results demonstrated that this technology can be used to statistically distinguish the different levels of devitalization in oyamel individuals. Research highlights: This is the first research in Mexico that use Thermal and Multiespectral high resolution information related with field data applied to Abies religiosa and provides a methodological precedent for identify forest decline symptoms.